1999
DOI: 10.1007/s000660050034
|View full text |Cite
|
Sign up to set email alerts
|

Daily Amifostine Given Concomitantly to Chemoradiation in Head and Neck Cancer

Abstract: Amifostine given before each fraction of radiotherapy over 6 weeks has no cumulative toxicity, was well tolerated and may reduce treatment induced oral mucositis. No tumor protective effect was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Grade 3 oral mucositis was reduced when compared to historical controls (40 versus 70 %) in patients who received 500 mg amifostine within 1 h before radiotherapy [11]. Oral mucositis was significantly lower in severity at all 10 Gy increments except 60 Gy and over in patients who received 300 mg amifostine before radiotherapy when compared with historical controls [39]. On the other hand, no significant benefit of the addition of amifostine in head and neck cancer chemoradiotherapy was reported in two studies [29,30].…”
Section: Head and Neck Chemoradiotherapy: Preventionmentioning
confidence: 86%
See 3 more Smart Citations
“…Grade 3 oral mucositis was reduced when compared to historical controls (40 versus 70 %) in patients who received 500 mg amifostine within 1 h before radiotherapy [11]. Oral mucositis was significantly lower in severity at all 10 Gy increments except 60 Gy and over in patients who received 300 mg amifostine before radiotherapy when compared with historical controls [39]. On the other hand, no significant benefit of the addition of amifostine in head and neck cancer chemoradiotherapy was reported in two studies [29,30].…”
Section: Head and Neck Chemoradiotherapy: Preventionmentioning
confidence: 86%
“…Oral mucositis was delayed and showed lower degrees at all 10 Gy increments except 60 Gy and over [39].…”
Section: High-dose Chemotherapy: Preventionmentioning
confidence: 96%
See 2 more Smart Citations
“…In studies by Epperly et al (1999), a time-dependent progression in pathologic fibrosis after irradiation koh et al 1995koh et al Clinical: misirlioglu et al 2007ozturk et al 2004ozturk et al Clinical: haddad et al 2005okunieff et al 2004;delanian et al 2003;lefaix et al 1999;delanian 1998Clinical: letur-konirsch et al 2002Amifostine Multiple Preclinical: vujaskovic et al 2002cClinical: veerasarn et al 2006;antonadou et al 2003, 2001komaki et al 2004;koukourakis et al 2001;phan et al 2001;movsas et al 2005;brizel et al 2000;trog et al 1999trog et al Preclinical: vujaskovic et al 2007 Superoxide dismutasebased strategies Radiation pneumonitis/fibrosis Preclinical: gauter-fleckenstein et al 2007; rabbani et al 2007c, 2007b, 2005; epperly et al 2004, 2002a; guo et al 2003 indicated increased IL-1 mRNA levels correlated with early radiation pneumonitis, followed by an increase in TGF-β during the development of fibrotic disease and mortality. Moreover, Epperly et al (2000b) found manganese-SOD plasmid/liposome complex could prevent DNA double-strand breaks, inhibit mitochondrial-dependent apoptosis, reduce vascular adhesion molecule expression (epperly et al 2002c), and decrease early onset of TGFβ, IL-1, and TNF-α mRNA levels (epperly et al 2000a), as well as improve median survival time (epperly et al 2000b).…”
Section: +mentioning
confidence: 96%